Pengaruh Krisis Ekonomi Terhadap Peningkatan Substitusi Mata Uang Di Indonesia (Study Empiris : 1997/III â 2002/II) - Anatan, Lina (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2003)
The issue of currency substitutions in Indonesia is a monetary phenomenon with implication for domestic by the negative changes in some macro economics variable particularly since the economic crisis 1997. The main propose of this research was to investigate factors Realâs Gross Domestic exchange rate, Expectation inflation, spread interest rate between domestic interest rate foreign rate, and dummy variable about exchange rate police especially after economy crisis 1997. The date to be used cover quarterly data form the 3quartal of 2002 the result of the analysis show that the spread the interest rate, expected and the dummy variable have significant impact to the currency substitution in Indonesia while the Real GDP and the exchange rate doesnât show direct influence for the model used.